Needs assessment for faculty development at an Egyptian medical school: a triangulation approach - Abdelkreem, Elsayed; Abo-Kresha, Seham A.; Ahmed, Emad A.; Ibrahim, Doaa; Hemdan, Shimaa B.; Abdellah, Mostafa A. (International Journal Of Community Medicine And Public Health, 2020)
Background: Faculty development (FD) is a core component of medical education, and needs assessment is central for planning effective FD programs. In the present study, we assessed the perceived development needs of medical faculty and the factors affecting these needs at an Egyptian medical school. Methods: This sequential mixed-methods research was conducted in 2019 at Faculty of Medicine, Sohag University (Egypt) using a triangulation approach for data collection: (1) web-based survey composed of 74 items about demographics and educational experiences, satisfaction with current FD programs, perceived development needs, delivery and scheduling preferences; (2) semi-structured interviews for in-depth understanding; and (3) secondary data. Results: A total of 434 out of 793 target faculty (54.7%) completed the survey. Participants in general perceived moderate to extreme need to all FD areas with the highest priorities given for discipline-specific and research domains. Awareness of teaching needs has increased among faculty in recent years. Perceived FD needs varied across career stage, and most participants preferred short interactive workshops; online methods are also desired. Compulsory participation in FD programs was a subject of high controversy. More than one-third of participants were interested in joining the newly established medical education department. Conclusions: Perceived FD needs are affected by accreditation standards, academic reward systems, and socioeconomic factors. The present study provides a transferrable model for conducting FD needs assessment, and the findings are important for planning effective and economically sound FD programs within the complex structure of today’s medical schools.